2022
DOI: 10.1002/jgh3.12789
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative risk of developing a new symptom in patients with primary biliary cholangitis and its impact on prognosis

Abstract: Background and Aim Symptoms of primary biliary cholangitis (PBC) frequently impair one's quality of life (QOL). Nonetheless, with improved treatment, the prognosis of PBC also improves. QOL plays an important role in patients with PBC. In this study, we aimed to reevaluate the transition of new symptom development in PBC and its predictive factors. Methods This retrospective multicenter study enrolled 382 patients with PBC for symptom analysis. The impact of a newly developed symptom on PBC prognosis was inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…We adopted the Paris II criteria in the present study, as they could predict overall survival, liver-related death, and future prevalence of symptoms in patients with PBC. 4,6 The percentage of patients who met the requirements in this study was approximately equivalent to that in previous reports; therefore, we believe that the results from this study are reproducible.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…We adopted the Paris II criteria in the present study, as they could predict overall survival, liver-related death, and future prevalence of symptoms in patients with PBC. 4,6 The percentage of patients who met the requirements in this study was approximately equivalent to that in previous reports; therefore, we believe that the results from this study are reproducible.…”
Section: Discussionsupporting
confidence: 85%
“…23,24 These studies did not use the Paris II criteria, which have been reported to be the best for prognosis prediction, to determine treatment response. 4,6 We reported that prothrombin time % and AST were the independent predictors for the Paris II criteria; however, ROC was 0.695 and 0.669, respectively. 6 The AUC for data 1 and 2 was >0.8, sufficiently high for use in actual clinical practice.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…As these studies aimed to predict the Barcelona, Paris I, or Toronto criteria, it is difficult to compare our results with theirs. However, previous reports have shown that Paris II criteria could predict OS, LRD, and newly developed symptoms in patients with PBC 16,17 . From these data, we deduced that our prediction model could be more useful than previous prediction models.…”
Section: Discussionmentioning
confidence: 67%
“…Treatment response at 12 months after initial UDCA treatment is recognized as a surrogate marker for early detection of high‐risk patients as per the guidelines. Well‐known methods to detect good treatment response are the Paris I, Paris II, Barcelona, and Ehime criteria 2,8,16,27 . We have reported previously that the Paris II criteria may be able to predict overall survival (OS), liver‐related deaths (LRD), and newly developed symptoms 17,31 .…”
Section: Introductionmentioning
confidence: 99%